Prostaglandin metabolism in the ovine corpus luteum - Silva, Patrick James, author; Niswender, Gordon, advisor; Whittier, Jack C., committee member; Sawyer, H. R., committee member; Tucker, Alan, committee member; Anthony, Russell V., committee member (Colorado State University. Libraries, 2000)
The goal of the research comprising this dissertation was to gain insight into the relative importance of luteal biosynthesis of prostaglandin and possible catabolism of PGF2α by the corpus luteum. Expression patterns of two enzymes (cyclooxygenase-2 and 15-hydroxyprostaglandin dehydrogenase) important to prostaglandin synthesis and catabolism are described herein. On day 4 post estrus and day 13 postcoitus, the ovine corpus luteum is resistant to the luteolytic effects of PGF2α, Thus, the primary biological question that inspired this research is: "What mechanisms allow the corpus luteum early in the estrous cycle and early in pregnancy to be resistant to the luteolytic activity of PGF2α?". Two potential mechanisms were addressed, decreased synthesis of PGF2α and catabolism of PGF2α in the corpus luteum. The first hypothesis tested was: "PGDH enzymatic activity is greater on day 4 of the estrous cycle and day 13 of pregnancy than on day 13 of the estrous cycle". Enzymatic activity of PGDH, measured by rate of conversion of PGF2α to PGFM, was greater in corpora lutea on both day 4 of the estrous cycle (p=0.03) and day 13 of pregnancy (p=0.05) than on day 13 of the estrous cycle. The inability of the corpus luteum to produce PGF2α may also play a role in resistance of the corpus luteum to the luteolytic actions of uterine PGF2α. Thus, the second hypothesis tested was that expression of mRNA encoding COX-2 will be attenuated on day 4 of the estrous cycle and day 13 of pregnancy relative to day 13 of the estrous cycle". Messenger RNA encoding COX-2 was undetectable (<3 amol/μg poly A+ RNA) in corpora lutea from ewes on day 13 of the cycle. In corpora lutea from ewes on day 4 of the estrous cycle, levels of mRNA encoding COX-2 were 43.77±27.75 amol/μg poly A+ RNA, while on day 13 of pregnancy levels of mRNA encoding COX-2 were 10.57± 4.41 amol/μg poly A+ RNA. The results of this research suggest that a novel mechanism, enhanced catabolism of PGF2α, plays a role in resistance of the corpus luteum to the luteolytic activity of PGF2α. The fact that increased PGDH activity occurs when resistance of the corpus luteum to the luteolytic activity of PGF2α is known to occur is an exciting advance in understanding luteal physiology and adaptations in luteal function during early pregnancy.
Keywords: anatomy and physiology; animals